Skin-Conformal Ag Flake-Decorated PEDOT:PSS Sensor Arrays for Spatially Resolved Body Temperature Monitoring - Hwang, Chuljin; Choi, Jun Gyu; Pang, Changhyun; Kim, Min Seok; Park, Sungjun (Small, 2025)
Rapid and spatial temperature measurement on the skin is essential for detecting localized physiological anomalies, such as inflammation or circulatory issues, while providing insights into thermoregulation. Skin-conformal temperature sensors, with ultra-flexible designs, enable precise and comfortable measurements, supporting real-time monitoring, early diagnosis, and effective intervention. However, achieving rapid and spatial skin-conformal temperature sensor arrays that simultaneously maintain high sensitivity under extreme mechanical stresses remains a significant challenge. This work introduces a skin-conformal temperature sensor array based on a composite of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) and Ag flakes, fabricated on a 2-µm-thick parylene-C substrate. A simple mixing process achieves uniform dispersion of Ag flakes, enhancing electrical conductivity to 2.04 kS cm−1. The sensor demonstrates a temperature coefficient of resistance of −2.02%/°C (30–50 °C), a resolution of 0.5 °C, and a rapid response time under 0.41 s per 5 °C change. It endures over 1000 cycles of 200% strain and performs reliably under 3 µm bending radii. Demonstrating high-resolution sensitivity and spatial temperature mapping through letter pattern recognition, the sensor shows promise for applications in body temperature monitoring, thermal imaging, and early diagnosis of temperature-related health conditions.
Keywords: Ethylenedioxythiophenes; Poly(styrene sulfonate); Polymer/metal composites; Real- time; Real-time temperature monitoring; Skin-conformal device; Temperature mapping; Temperature monitoring; Temperature sensor array; Time-temperature; polymer-metal composite; real-time temperature monitoring; skin-conformal device; temperature mapping; temperature sensor array